Caffeic Acid Phenethyl Ester Reduces Ischemia-Induced Kidney Mitochondrial Injury in Rats. (13th August 2017) - Trumbeckaite, Sonata; Pauziene, Neringa; Trumbeckas, Darius; Jievaltas, Mindaugas; Baniene, Rasa
Abstract : During partial nephrectomy, the avoidance of ischemic renal damage is extremely important as duration of renal artery clamping (i.e., ischemia) influences postoperative kidney function. Mitochondria (main producer of ATP in the cell) are very sensitive to ischemia and undergo damage during oxidative stress. Finding of a compound which diminishes ischemic injury to kidney is of great importance. Caffeic acid phenethyl ester (CAPE), biologically active compound of propolis, might be one of the promising therapeutic agents against ischemia-caused damage. Despite wide range of biological activities of CAPE, detailed biochemical mechanisms of its action at the level of mitochondria during ischemia are poorly described and need to be investigated. We investigated if CAPE (22 mg/kg and 34 mg/kg, injected intraperitoneally) has protective effects against short (20 min) and longer time (40 min) rat kidney ischemia in an in vitro ischemia model. CAPE ameliorates in part ischemia-induced renal mitochondrial injury, improves oxidative phosphorylation with complex I-dependent substrate glutamate/malate, increases Ca 2+ uptake by mitochondria, blocks ischemia-induced caspase-3 activation, and protects kidney cells from ischemia-induced necrosis. The protective effects on mitochondrial respiration rates were seen after shorter (20 min) time of ischemia whereas reduction of apotosis and necrosis and increase in Ca 2+ uptake were revealed after both, shorter and longer time of ischemia.